A Day in the Life of Design—at the US Digital Service. (22nd February 2016) - Chisnell, Dana
Abstract : She came in as a design researcher from the private sector. Now she's one of a team helping to bring user‐centered design to government agencies. She sees the USDS as an important place for designers to be, and to make themselves known. Even the daily planning meeting wasn't able to kill the sheer pleasure of seeing design make a difference in the working life of The Business.